2014
DOI: 10.1080/19424280.2014.890671
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for gender-specific soccer shoe development

Abstract: To date, there is a lack of research on gender-specific soccer footwear, even though there are biological differences as well as differences in playing behaviour among female and male players. This paper discusses criteria that are important for the development of women-specific soccer shoes. Females are different in size and body composition and due to a lower muscular strength, movements are less powerful. Biomechanical and neuromuscular differences are the cause of different movement patterns and in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
2
4
0
Order By: Relevance
“…Our results showed that the t and comfort of badminton shoes were recognized as the most important shoe feature in both males and females. This is similar to previous research on running, soccer, gym, basketball and tennis footwear, which also indicate t and comfort as the most important shoe features [1,[11][12][13][14]. Moreover, it has been shown that footwear comfort has signi cant in uences on lower limb injuries and performances.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results showed that the t and comfort of badminton shoes were recognized as the most important shoe feature in both males and females. This is similar to previous research on running, soccer, gym, basketball and tennis footwear, which also indicate t and comfort as the most important shoe features [1,[11][12][13][14]. Moreover, it has been shown that footwear comfort has signi cant in uences on lower limb injuries and performances.…”
Section: Discussionsupporting
confidence: 89%
“…Footwear structural features have the potential to affect comfort and athletic performances [10]. Sport shoe characteristics for running, gym, football, basketball, and tennis have been previously studied using questionnaires [1,[11][12][13][14], but information for badminton has not been established. Movement mechanics and loading characteristics in badminton are clearly different from running and other court sports, resulting in distinct requirements of footwear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the fit and comfort of badminton shoes were recognized as the most important shoe feature in both males and females. This is similar to previous research on running, soccer, gym, basketball and tennis footwear, which also reported fit and comfort as the most important shoe features [1, 11–14]. Moreover, another research studying shoe comfort during standing tasks, preferred footwear conditions were shown to result in the lowest levels of lower extremity and back pain.…”
Section: Discussionsupporting
confidence: 88%
“…Several investigations show that female feet were not just a scaled down version of male feet [ 18 , 19 ] and female feet were characterized by a higher arch, shallower first toe, shorter length of the outside ball and smaller instep circumference. Other etiological factors including hip Q-angle, foot shape, body mass, muscle strength are different between genders [ 13 ], which results in distinct biomechanical alternations and thereby different footwear requirements between males and females [ 11 ]. Therefore, it can be assumed that badminton shoes need to be optimized with reference to these characteristics between genders in badminton.…”
Section: Introductionmentioning
confidence: 99%